A FACE CAMONIANA EM ERROS MEUS, MÁ FORTUNA, AMOR ARDENTE, DE NATÁLIA CORREIA - Barausse, Sibele (2021)
The figure of Luís Vaz de Camões certainly represents one of the most important names in Portuguese-language literature. Mainly, to the Portuguese, he is the biggest icon, the one who sang the history of Portugal and made it recognized through his verses. There are many biographies and the attempt to register the life of this writer, despite of the uncertainty related to his life. In the celebration of the fourth centenary of his death in 1980, the Dona Maria II National Theater ordered plays that would resume the life of the poet, and among the guests was Natália Correia, who wrote the play Erros Meus, Má Fortuna, Amor Ardente (1981). However, because of structural and political reasons, Natália’s play was not staged during the event, and it was released only in 1981 in a luxury edition by the publisher Afrodite. The play that is the corpus of the analysis of this work is based on Camões’ works and builds a biographical path through the camonian verses but using the dramatic genre. Thus, a symbiosis of textual genres: lyrics, epic, drama, and biography is used in the attempt of portraying Camões. By proposing this path, the writer subverts the biographical genre and uses the dramatic and lyric genre to build her work. This work aims at analyzing the play in order to unveil the particularities of Natália Correia’s writing and the strategies she is based onto build and present the character Luís Vaz de Camões, among many faces, the one that Natália Correia emphasizes the most is lyrics.